High expression of folate metabolic pathway gene MTHFD2 is related to the poor prognosis of patients and may apply as a potential new target for therapy of NSCLC - Zhang Xin; Yang Peiying; Meng Guangxian (Pteridines, 2025)
Data mining was applied to explore the expression, functional enrichment, and signal pathway of methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) gene in non-small cell lung cancer (NSCLC) and its relationship with patient prognosis.